Preparation method and application of 2D / 2D heterostructure wave-absorbing material based on solvent regulation and control growth
By preparing ZnIn2S4/Bi4NbO8Cl heterostructure absorbing material coexposed with high activity {001} and {110} crystal planes, the problem of difficulty in removing OTC pollutants in the environment is solved, and efficient catalytic degradation of OTC with microwave assistance is achieved, which is highly efficient, environmentally friendly and low energy consumption.
Patent Information
- Application Number
- CN202510076995.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-29
AI Technical Summary
Residual antibiotics such as oleracin hydrochloride (OTC) in the environment pose a threat to human health, and the prior art is difficult to remove these pollutants efficiently, especially on the premise of reducing energy consumption and shortening reaction time.
The 2D/2DZnIn2S4/Bi4NbO8Cl heterostructure absorbing material was prepared by co-exposed 2D/2DZnIn2S4/Bi4NbO8Cl heterostructured absorbing material with microwave assistance, and the catalytic degradation of OTC was performed.
It is achieved efficient degradation of OTC by microwave-assisted catalysis under normal pressure of 80°C, which significantly improves carrier separation efficiency and catalytic activity, and reduces energy consumption and reaction time.
Smart Images

Figure CN119900068A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of preparation of absorbing materials, and specifically relates to a preparation method of a 2D / 2D ZnIn2S4 / Bi4NbO8Cl heterostructure absorbing material with co-exposed {001} and {110} crystal planes and its application in oxytetracycline degradation. Background Art
[0002] The widespread use of antibiotics has triggered a series of potential problems closely related to environmental toxicity and microbial resistance. Oxytetracycline hydrochloride (OTC), as one of the main antibiotics, is widely present in natural water, soil and other media. It is particularly noteworthy that residual OTC in the environment may affect human health through accumulation in the food chain, leading to joint diseases, endocrine disorders, kidney diseases and cancer, thus causing inevitable damage to the human body. Therefore, it is of great significance to develop wastewater treatment technologies with excellent performance to remove residual antibiotics in the environment.
[0003] Microwave (MW) induced catalytic technology has the advantages of rapid and uniform heating and elimination of temperature gradients, providing a feasible solution for improving treatment efficiency, reducing energy consumption and shortening reaction time. This is consistent with the goals of energy saving and high-performance water treatment. Compared with traditional wastewater treatment methods, MW induced catalytic technology circumvents challenges such as sludge bulking, residual sludge treatment and secondary pollution. However, the effective design of MW catalysts is the key to improving the efficiency of MW induced catalysis. Bi4NbO8Cl is a new type of layered bismuth-based oxyniobate halide. Due to its high structural symmetry, unique layered structure, alternating [Bi2O2] 2+ Layer and Cl - The layer is conducive to carrier separation and interlayer migration of materials, and has good MW absorption performance. Due to the anisotropy of different crystal planes of Bi4NbO8Cl, its charge separation and aggregation properties can be regulated by regulating the degree of crystal plane exposure. The co-exposure of its {001} and {110} highly active crystal planes can form a well-matched crystal plane junction, realizing efficient spatial separation of photogenerated electrons and holes. In order to further improve the efficiency of carrier separation and extend the carrier lifetime, constructing a heterojunction is also a very effective way. ZnIn2S4, as a ternary metal sulfide semiconductor, is widely recognized for its unique tunable band gap (2.06-2.85eV) and excellent thermodynamic stability. In addition, ZnIn2S4 has a more negative conduction band value, which makes it more reducible. Therefore, the heterojunction composite material constructed by these two semiconductors will have a high catalytic potential. In this paper, a highly active ZnIn2S4 / Bi4NbO8Cl heterojunction absorber with co-exposed {001} and {110} crystal planes was successfully prepared through the molten salt and oil bath method, and it exhibited excellent catalytic activity in the MW synergistic catalytic degradation of OTC. Summary of the invention
[0004] To achieve the above objectives, the present invention provides a method for preparing a 2D / 2DZnIn2S4 / Bi4NbO8Cl heterostructure absorbing material with co-exposed {001} and {110} crystal planes and its application in the degradation of oxytetracycline.
[0005] The technical solution adopted by the present invention is:
[0006] A method for preparing a 2D / 2D heterostructure absorbing material based on solvent-controlled growth comprises the following steps:
[0007] 1) Preparation of 2D plate-like Bi4NbO8Cl: BiOCl, Bi2O3, Nb2O5, LiCl and KCl were mixed and ground in an agate mortar. The ground mixed powder was placed in an alumina crucible with a lid and calcined at 750°C for 6 hours. The obtained powder was naturally cooled, repeatedly rinsed with deionized water to remove residual LiCl and KCl, and dried in an oven at 80°C overnight to obtain a Bi4NbO8Cl absorber with mainly exposed {001} and {110} highly active crystal planes, denoted as BNOC;
[0008] 2) Preparation of ZnIn2S4 / Bi4NbO8Cl absorbing material: ZnCl2, InCl3·4H2O and thioacetamide were dissolved in a solvent, and the BNOC prepared in step 1) was added. After ultrasonic dispersion, the mixture was stirred and heated in an oil bath at 80°C for 2 h. The precipitate was washed and dried to obtain the ZnIn2S4 / Bi4NbO8Cl absorbing material, which was denoted as ZIS / BNOC.
[0009] Furthermore, in the above preparation method, in step 1), the amount of BiOCl used is 0.2604 g, the amount of Bi2O3 used is 0.6989 g, the amount of Nb2O5 used is 0.1329 g, the amount of LiCl used is 0.4239 g, and the amount of KCl used is 0.7455 g.
[0010] Furthermore, in the above preparation method, in step 2), the solvent is ethanol, water, or a mixed solution of ethanol and water in a volume ratio of 1:1.
[0011] Preferably, in step 2), the solvent is ethanol.
[0012] Furthermore, in the above-mentioned preparation method, in step 2), the mass proportion of ZnIn2S4 in ZnIn2S4 / Bi4NbO8Cl is 7% to 20%.
[0013] Preferably, in step 2), the mass proportion of ZnIn2S4 in ZnIn2S4 / Bi4NbO8Cl is 10%.
[0014] Application of a 2D / 2D heterostructure absorbing material based on solvent-regulated growth prepared by any of the preparation methods described above in the degradation of oxytetracycline.
[0015] Further, the above application, the method is as follows: take 50mL 10mg L -1 The OTC solution was placed in a three-necked flask, the pH value of the solution was adjusted to 4.7, and ZnIn2S4 / Bi4NbO8Cl absorbing material was added to catalyze the degradation of OTC at a microwave power of 700 W.
[0016] Furthermore, in the above application, the added amount of the ZnIn2S4 / Bi4NbO8Cl absorbing material is 15 mg.
[0017] Furthermore, in the above application, the time for catalytic degradation of OTC is 5 minutes.
[0018] The beneficial effects of the present invention are:
[0019] 1. The present invention loads 2D ZnIn2S4 nanosheets on 2D plate-like Bi4NbO8Cl with highly active {001} and {110} co-exposed crystal planes by changing the solvent composition under normal pressure and 80°C, thereby constructing a 2D / 2D ZnIn2S4 / Bi4NbO8Cl heterostructure with different morphologies, which can efficiently degrade the environmental pollutant OTC under the assistance of microwaves.
[0020] 2. The ZIS / BNOC-Y heterojunction prepared by the present invention exhibits enhanced catalytic activity for OTC compared to its monomer; and the prepared ZIS / BNOC-Y has higher catalytic activity than ZIS / BNOC-H and ZIS / BNOC-S. The present invention provides a control idea for material design, which is helpful to promote the application of microwave catalysis technology in the field of environmental purification. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 (a) is the XRD spectrum of BNOC prepared in Example 1 and ZIS prepared in Example 2, (b) is the XRD spectrum of BNOC and 10% ZIS / BNOC-Y prepared in Example 1, 10% ZIS / BNOC-S prepared in Example 6, and 10% ZIS / BNOC-H prepared in Example 7.
[0022] Figure 2 SEM images of BNOC (a) and 10% ZIS / BNOC-Y (b) prepared in Example 1, 10% ZIS / BNOC-H (c) prepared in Example 7, and 10% ZIS / BNOC-S (d) prepared in Example 6.
[0023] Figure 3 It is a comparison chart of the OTC degradation efficiency of 10% ZIS / BNOC-Y prepared in Example 1, 10% ZIS / BNOC-S prepared in Example 6 and 10% ZIS / BNOC-H prepared in Example 7. DETAILED DESCRIPTION
[0024] Example 1 Preparation of ZnIn2S4 / Bi4NbO8Cl Absorbing Material
[0025] 1) Preparation of 2D plate-like Bi4NbO8Cl: 0.2604g BiOCl, 0.6989g Bi2O3, 0.1329g Nb2O5, 0.4239g LiCl and 0.7455g KCl were mixed and ground in an agate mortar. The ground mixed powder was placed in an alumina crucible with a lid and calcined at 750°C for 6 hours. The obtained powder was cooled naturally, repeatedly rinsed with deionized water to remove residual LiCl and KCl, and dried in an oven at 80°C overnight to obtain a Bi4NbO8Cl absorber material with mainly exposed {001} and {110} highly active crystal planes, denoted as BNOC.
[0026] 2) Preparation of ZnIn2S4 / Bi4NbO8Cl absorbing material: 0.0179 g ZnCl2, 0.0770 g InCl3·4H2O, and 0.0493 g thioacetamide (TAA) were weighed respectively and dissolved in 30 mL ethanol, and then 0.500 g of the prepared BNOC was added. After ultrasonic dispersion, it was stirred and heated in an oil bath at 80°C for 2 h. The precipitate was washed and dried to obtain a ZnIn2S4 / Bi4NbO8Cl absorbing material with a ZnIn2S4 content of 10%, which was recorded as 10% ZIS / BNOC-Y.
[0027] Example 2
[0028] Preparation of ZIS: Weigh 0.0682g ZnCl2, 0.2932g InCl3·4H2O, and 0.1878g thioacetamide (TAA) respectively and dissolve them in 30mL ethanol. After ultrasonic dispersion, stir and heat in an 80℃ oil bath for 2h. Wash and dry the precipitate to obtain the ZnIn2S4 absorbing material, which is recorded as ZIS.
[0029] Example 3
[0030] 7% ZIS / BNOC-Y was synthesized according to the preparation method in Example 1, except that the addition amounts of some raw materials were changed to: 0.0121 g ZnCl2, 0.0521 g InCl3·4H2O, 0.0331 g TAA.
[0031] Example 4
[0032] According to the preparation method of Example 1, only the addition amount of some raw materials was changed to: 0.0284g ZnCl2, 0.1223g InCl3·4H2O, 0.0783g TAA, to synthesize 15% ZIS / BNOC-Y.
[0033] Example 5
[0034] According to the preparation method of Example 1, only the addition amount of some raw materials was changed to: 0.0403g ZnCl2, 0.1732g InCl3·4H2O, 0.1109g TAA, to synthesize 20% ZIS / BNOC-Y.
[0035] Example 6
[0036] According to the preparation method of Example 1, except that the 30 mL of ethanol in step 2) was replaced with 30 mL of water, 10% ZIS / BNOC-S was synthesized.
[0037] Example 7
[0038] According to the preparation method of Example 1, except that the 30 mL of ethanol in step 2) was replaced with a mixed solution of 15 mL of ethanol + 15 mL of water, 10% ZIS / BNOC-H was synthesized.
[0039] Material characterization
[0040] Figure 1 XRD patterns of different samples. Figure 1 a It can be seen that the diffraction peaks of the BNOC sample at 2θ=12.30°, 22.87°, 23.70°, 29.58°, 31.08°, 31.68° and 32.58° are respectively attributed to the (004), (110), (112), (116), (0010), (117) and (020) crystal planes of Bi4NbO8Cl (JCPDS No.84-0843), indicating that the Bi4NbO8Cl sample was successfully synthesized, and the {001} and {110} active crystal planes were co-exposed. The diffraction peaks of the ZIS sample at 2θ=21.58°, 27.69° and 39.77° correspond to the (006), (102) and (108) crystal planes of ZnIn2S4 (JCPDS No.65-2023), respectively, proving that ZnIn2S4 was successfully synthesized. Figure 1 b As can be seen, in the composite material, a weak and broad new diffraction peak appears at 2θ=21.58°, proving the successful loading of ZnIn2S4. The weak peak intensity mainly comes from the weaker diffraction of pure ZIS and its lower loading amount in the composite material.
[0041] Figure 2 SEM images of various materials. Figure 2 a It can be observed that BNOC presents a 2D plate-like structure with a size of 3-4 μm and a thickness of about 200 nm. Figure 2 b is the SEM image of 10% ZIS / BNOC-Y composite material, where it can be seen that fine 2D nanosheet ZIS grows tightly and evenly on the 2D plate-like BNOC surface. Figure 2 c is the SEM image of 10% ZIS / BNOC-H composite material synthesized from ethanol / water mixed solution, with small 2D nanosheets spread on the 2D plate-like BNOC surface. Figure 2 d is the SEM image of the 10% ZIS / BNOC-S composite synthesized in pure aqueous solution, where thin and large 2D nanosheets grow loosely and evenly on the 2D plate-like BNOC surface. It can be seen that different synthetic solvents have a significant effect on the morphology of ZIS / BNOC composites.
[0042] Example 8
[0043] (I) Catalytic degradation experiment
[0044] Catalytic degradation experiments were carried out in a laboratory-specific microwave instrument, whose temperature, power, and reaction time were controllable and equipped with a condensation reflux device. -1 The OTC standard solution was placed in a 250 mL three-necked flask, the pH value of the solution was adjusted to 4.7, 15 mg of ZnIn2S4 / Bi4NbO8Cl absorbing material was added, and OTC was catalytically degraded at a microwave power of 700 W. Samples were taken every 1 minute to test the change in OTC content.
[0045] (II) MW-driven ZnIn2S4 / Bi4NbO8Cl catalytic activity
[0046] As shown in Table 1, the degradation effect of MW radiation alone on OTC is almost negligible; the degradation rate of OTC adsorbed by 10% ZIS / BNOC-Y alone for 5 minutes is only 20.5%; the degradation rate of OTC by BNOC monomer under MW drive is 31.4% within 5 minutes; the degradation rate of OTC by ZIS monomer under MW drive is 28.0% within 5 minutes; the degradation rate of OTC by 10% ZIS / BNOC-Y absorber under MW drive can reach 93.6% within 5 minutes, showing ultra-high MW-induced catalytic activity.
[0047] Table 1 Comparison of OTC degradation effects of different methods within 5 min
[0048]
[0049] (III) Effect of different solvents for synthesizing ZnIn2S4 / Bi4NbO8Cl on OTC degradation
[0050] like Figure 3 As shown, the effect of different synthesis solvents on the efficiency of ZnIn2S4 / Bi4NbO8Cl synergistic MW degradation of OTC was investigated. The results showed that when the synthesis solvent was pure ethanol, the degradation efficiency of the obtained 10% ZIS / BNOC-Y absorbing material was the highest.
[0051] (IV) Effect of catalyst dosage on OTC degradation
[0052] The following parameters were kept constant in the catalytic degradation experiment: OTC concentration was 10 mg L -1 , MW power 700W. 5mg, 10mg, 15mg and 20mg of 10% ZIS / BNOC-Y were added to 50mL solution respectively. As shown in Table 2, with the increase of catalyst dosage, the degradation efficiency also increased. When the dosage was 15mg, the degradation rate of OTC could reach 93.6% after microwave irradiation for 5min. Further increase of dosage did not significantly improve the catalytic efficiency.
[0053] Table 2 Effect of catalyst dosage on OTC degradation effect
[0054]
[0055] (V) Effect of reaction time on OTC degradation
[0056] The following parameters were kept constant in the catalytic degradation experiment: OTC concentration was 10 mg L -1 , MW power 700W, add 15mg 10% ZIS / BNOC-Y to 50mL OTC solution. As shown in Table 3, with the extension of MW irradiation time, the degradation efficiency also increases. After MW irradiation for 5min, the degradation rate can reach 93.6%. Further extension of the reaction time does not significantly improve the catalytic efficiency.
[0057] Table 3 Effect of MW irradiation time on OTC degradation effect
[0058]
[0059] (VI) Effect of ZnIn2S4 loading on OTC degradation
[0060] In order to investigate the effect of ZnIn2S4 loading on catalytic efficiency, 50 mL of 10 mg L -1 The OTC solution was placed in a 250 mL three-necked round-bottom flask, and then 15 mg of ZIS / BNOC-Y absorbing material with ZnIn2S4 loading of 7%, 10%, 15% and 20% by mass was added to the round-bottom flask, and MW radiation (700 W) was turned on.
[0061] As shown in the results in Table 4, under MW radiation, the catalytic degradation effect of ZIS / BNOC-Y on OTC showed a trend of first increasing and then decreasing with the increase of ZnIn2S4 loading. The ZIS / BNOC-Y catalyst with a ZnIn2S4 loading of 10% had the best degradation efficiency of OTC within 5 minutes.
[0062] Table 4 Effect of different ZnIn2S4 loading on OTC degradation
[0063]
[0064] (VII) Effect of different solution pH values on OTC degradation
[0065] As shown in Table 5, in order to explore the effect of solution pH on the catalytic degradation performance of OTC, the solution pH was adjusted to 2, 4.7, 7 and 10, respectively, and the catalytic reaction was carried out. The results showed that as the pH decreased from 10 to 4.7, the degradation efficiency of 10% ZIS / BNOC-Y on OTC increased, and the catalytic activity was optimal when the pH was 4.7. Further reducing the pH to 2, the catalytic activity decreased.
[0066] Table 5 Effect of different pH on OTC degradation
[0067]
Claims
1. A method for preparing a 2D / 2D heterostructure absorbing material based on solvent-controlled growth, characterized in that: The following steps are involved: 1) Preparation of 2D plate-like Bi4NbO8Cl: BiOCl, Bi2O3, Nb2O5, LiCl and KCl were mixed and ground in an agate mortar. The ground mixed powder was placed in an alumina crucible with a lid and calcined at 750°C for 6 hours. The obtained powder was naturally cooled, repeatedly rinsed with deionized water to remove residual LiCl and KCl, and dried in an oven at 80°C overnight to obtain a Bi4NbO8Cl absorber with mainly exposed {001} and {110} highly active crystal planes, denoted as BNOC; 2) Preparation of ZnIn2S4 / Bi4NbO8Cl absorbing material: ZnCl2, InCl3·4H2O and thioacetamide were dissolved in a solvent, and the BNOC prepared in step 1) was added. After ultrasonic dispersion, the mixture was stirred and heated in an oil bath at 80°C for 2 h. The precipitate was washed and dried to obtain the ZnIn2S4 / Bi4NbO8Cl absorbing material, which was denoted as ZIS / BNOC.
2. The preparation method according to claim 1, characterized in that: In step 1), the amount of BiOCl used is 0.2604 g, the amount of Bi2O3 used is 0.6989 g, the amount of Nb2O5 used is 0.1329 g, the amount of LiCl used is 0.4239 g, and the amount of KCl used is 0.7455 g.
3. The preparation method according to claim 1, characterized in that: In step 2), the solvent is ethanol, water, or a mixed solution of ethanol and water in a volume ratio of 1:
1.
4. The preparation method according to claim 3, characterized in that: In step 2), the solvent is ethanol.
5. The preparation method according to claim 1, characterized in that: In step 2), the mass proportion of ZnIn2S4 in ZnIn2S4 / Bi4NbO8Cl is 7% to 20%.
6. The preparation method according to claim 5, characterized in that: In step 2), the mass proportion of ZnIn2S4 in ZnIn2S4 / Bi4NbO8Cl is 10%.
7. Application of a 2D / 2D heterostructure absorbing material based on solvent-regulated growth prepared by the preparation method described in any one of claims 1 to 6 in the degradation of oxytetracycline.
8. The use according to claim 7, characterized in that: The method is as follows: Take 50mL of 10mg L -1 The OTC solution was placed in a three-necked flask, the pH value of the solution was adjusted to 4.7, and ZnIn2S4 / Bi4NbO8Cl absorbing material was added to catalyze the degradation of OTC at a microwave power of 700 W.
9. The use according to claim 8, characterized in that: The added amount of the ZnIn2S4 / Bi4NbO8Cl absorbing material is 15 mg.
10. The use according to claim 8, characterized in that: The time for catalytic degradation of OTC is 5 minutes.
Citation Information
Cited By
Cu-S-Bi4NbO8Br photocatalyst as well as preparation method and application thereof
CN121534747A
Cu-s-bi4nbo8br photocatalyst, preparation method and application thereof
CN121534747B